Catalogo de los Dipetra de Nicaragua. 2. Psychodidae (Nematocera) - Maes, J.-M.=700 1 Killick-Kendrick, R.
(En, Es)
Ilus., 93 ref.
Keywords: CLASIFICACION; DIPTERA; INSECTA; PSYCHODIDAE; HUESPEDES; ENEMIGOS NATURALES; DISTRIBUCION GEOGRAFICA; NICARAGUA; NEMATOCERA; REVISTA NICARAGUENSE DE ENTOMOLOGIA